Conductivity enhancement via chemical modification of chitosan based green polymer electrolyte - Mobarak N.N.; Ahmad A.; Abdullah M.P.; Ramli N.; Rahman M.Y.A. (2023)
The potential of carboxymethyl chitosan as a green polymer electrolyte has been explored. Chitosan produced from partial deacetylation of chitin was reacted with monochloroacetic acid to form carboxymethyl chitosan. A green polymer electrolyte based chitosan and carboxymethyl chitosan was prepared by solution-casting technique. The powder and films were characterized by reflection Fourier transform infrared (ATR-FTIR) spectroscopy, 1H nuclear magnetic resonance, elemental analysis and X-ray diffraction, electrochemical impedance spectroscopy, and scanning electron microscopy. The shift of wavenumber that represents hydroxyl and amine stretching confirmed the polymer solvent complex formation. The XRD spectra results show that chemical modification of chitosan has improved amorphous properties of chitosan. The ionic conductivity was found to increase by two magnitudes higher with the chemical modification of chitosan. The highest conductivity achieved was 3.6 10-6 S cm-1 for carboxymethyl chitosan at room temperature and 3.7 10-4 S cm-1 at 60 C. 2013 Elsevier Ltd.